Lateral Reinforcement in Prestressed Concrete Poles - Singh P.K.; Verma R.J. (My University, 2025)
Prestressed concrete power transmission poles are widely manufactured in India. Transverse untensioned reinforcement in the poles is provided on the basis of past practice which is insufficient from the considerations of confinement of concrete, bursting tensile force and minimum stirrup requirement. For a typical pole of 8.5 m height, requirement of the transverse reinforcement based on these consideration is presented. Provision of adequate transverse reinforcement is expected to avoid local damage to the poles during manufacture, transportation, erection and service stage. Hollow circular prestressed concrete poles having transverse reinforcement in the form of spiral steel are expected to be much more efficent than the solid rectangular poles. Damage to other precast prestressed concrete members, such as railway sleepers, can also be significantly brought down by providing adequete transverse untensioned reinforcement based on similar considerations.